Systematic review and meta‐analysis of the performance of nurses in small bowel capsule endoscopy reading. Issue 8 (1st December 2017) - Yung, Diana E; Fernandez‐Urien, Ignacio; Douglas, Sarah; Plevris, John N; Sidhu, Reena; McAlindon, Mark E; Panter, Simon; Koulaouzidis, Anastasios
Abstract : Introduction: Increasing demands on healthcare systems mean that nurses are taking on more roles as physician extenders. Capsule endoscopy (CE) is a laborious procedure where specialist nurses could reduce physician workload and rationalise resource utilisation. The aim of this review and meta‐analysis is to consolidate data on nurses' performance in small bowel CE (SBCE). Materials and methods: A comprehensive literature search was conducted for randomised controlled trials and comparative studies on nurses in SBCE reading compared to physicians. We examined the performance of nurses compared to SBCE‐trained physicians. Results: Sixteen relevant studies were identified, with 820 SBCE examinations involving 20 nurses. 11/16 studies reported the numbers of SBCE findings detected. Overall, the pooled proportion of all findings reported by physicians and nurses was 86%. Studies involving nurses with endoscopic experience showed a summative detection rate of 89%. 7/16 studies reported the number of videos where there was agreement between the nurse and physicians for overall findings/diagnosis. The overall proportion of videos with agreement was 68%. In studies where nurses had endoscopy experience, the proportion of videos with agreement was 71%. Conclusion: Our meta‐analysis supports a more active role for nurses in SBCE reading. We suggest nurses can function as independent CE readers in general, given adequate training and formal credentialing.